The effect of social media marketing toward purchase intention of domestic tourists at Indigo Bali Seminyak Beach Hotel - Ni Putu Ariska Widhiasih; Ni Luh Gde Sri Sadjuni; Ni Luh Ketut Sri Sulistyawati (Universitas Pendidikan Nasional, 2025)
Purchase intention is a key factor that influences consumers in making purchasing decisions. One strategy thathas proven effective in increasing purchase intention is social media marketing. Hotel Indigo Bali Seminyakactively utilizes social media platforms, particularly Instagram and Facebook, to promote its brand and engagewith potential customers. This study aims to examine the effect of the hotel's social media marketing efforts onthe purchase intentions of domestic tourists. The research used a combination of documentation and surveymethods, with questionnaires distributed to 90 domestic tourist respondents. The data were analyzed usingvalidity and reliability tests, classical assumption testing, and simple linear regression. The results show that socialmedia marketing has a significant and positive impact on purchase intention. These findings highlight theimportance of maintaining an active and engaging presence on social media, as it can strongly influence consumerinterest and behavior. For hospitality businesses, investing in strategic social media campaigns can be a valuabletool in attracting and converting potential customers.